Pengaruh peran suami dan pijat oksitosin terhadap kelancaran ASI pada ibu nifas - Kartika, Jenny; Kamalia, Rita; Putri, Nia Clarasari Mahalia (Holistik Jurnal Kesehatan, 2025)
Background: Postpartum mothers often experience complaints, one of which is irregular breast milk flow. The preliminary research sample in this study was taken from secondary data from postpartum mothers' notebooks of 95 respondents, some respondents stated that breast milk was irregular and did not know the benefits of oxytocin massage. Efforts that can be made to provide smooth breast milk for postpartum mothers are oxytocin massage performed by health workers or husbands. Purpose: To determine the relationship between the role of the husband and oxytocin massage on smooth breast milk flow in postpartum mothers. Method: Quantitative research with a Cross Sectional design, conducted at the Independent Practice of Midwife Semiyati, Muara Enim Regency on January 1 - May 31, 2025. The independent variables consisted of the role of the husband and oxytocin massage, while the dependent variable was smooth breast milk flow. The sampling technique used purposive sampling and data were analyzed using the chi square test. Results: The role of the husband is most involved in oxytocin massage as many as 63 respondents (66.3%) with a smooth breastfeeding category of 50 respondents (82.0%), while the husband is not involved in providing oxytocin massage, most of the breast milk is not smooth as many as 21 respondents (61.8%). The results of the statistical analysis obtained a p value of 0.000, meaning that there is a significant relationship between the role of the husband and oxytocin massage on the smoothness of breast milk in postpartum mothers. Conclusion: There is a significant relationship between the role of the husband and oxytocin massage on the smoothness of breast milk with a sig value (2-tailed) of 0.000 (<0.05). Suggestion: It is hoped that the role of the husband and oxytocin massage can continue to be utilized as an alternative therapy to increase the smoothness of breast milk in postpartum mothers. In addition, for further researchers, they can conduct similar studies with other variables that are suspected of being able to affect the smoothness of breast milk in postpartum mothers.   Keywords: Oxytocin Massage; Role of Husband; Smooth Breast Milk Flow.   Pendahuluan: Ibu nifas banyak mengalami keluhan, salah satunya adalah ketidaklancaran ASI. Studi pendahuluan pada penelitian ini, sampel diambil dari data skunder dari buku pencatatan ibu nifas, terdapat 95 responden, sebagian responden mengatakan bahwa ASI tidak lancar dan belum mengetahui tentang manfaat pijat oksitosin. Upaya yang dapat dilakukan untuk memberikan kelancaran ASI ibu nifas yaitu dengan pemijatan oksitosin yang dilakukan oleh tenaga kesehatan maupun suami. Tujuan: Untuk mengetahui hubungan peran suami dan pijat oksitosin terhadap kelancaran ASI pada ibu nifas. Metode: Penelitian kuantiatif menggunakan desain Cross Sectional, dilaksanakan di PMB Semiyati Kecamatan Muara Enim pada tanggal 1 Januari - 31 Mei 2025. Variabel independen terdiri dari peran suami dan pijat oksitosin, sedangkan variabel dependen yaitu kelancaran ASI. Teknik pengambilan sampel menggunakan purposive sampling dan data dianalisis menggunakan uji chi-square. Hasil: Peran suami sebagian besar terlibat dalam pemijatan oksitosin sebanyak 63 responden (66.3%) dengan kategori ASI lancar sebanyak 50 responden (82.0%), sedangkan suami tidak terlibat dalam memberikan pijat oksitosin, sebagian besar ASI tidak lancar sebanyak 21 responden (61.8%). Hasil anlisis statistik ditemukan bahwa perolehan nilai p 0.000, artinya ada hubungan yang signifikan antara peran suami dan pijat eksitosin terhadap kelancaran ASI pada ibu nifas. Simpulan: Terdapat hubungan yang signifikan antara peran suami dan pijat oksitosin terhadap kelancaran ASI dengan nilai sig (2-tailed) 0.000 (< 0.05). Saran: Diharapkan peran suami dan pijat oksitosin dapat terus dimanfaatkan sebagai salah satu terapi alternatif untuk meningkatkan kelancaran ASI pada ibu nifas. Selain itu, peneliti selanjutnya dapat melakukan penelitian yang serupa dengan variabel lainnya yang diduga berpengaruh terhadap kelancaran ASI pada ibu nifas.   Kata Kunci: Kelancaran ASI; Peran Suami; Pijat Oksitosin.